Effects of six carbohydrate sources on diet digestibility and postprandial glucose and insulin responses in cats - de-Oliveira, L. D. [UNESP]; Carciofi, A. C. [UNESP]; Oliveira, M. C. C. [UNESP]; Vasconcellos, R. S. [UNESP]; Bazolli, R. S. [UNESP]; Pereira, G. T. [UNESP]; Prada, F. (Amer Soc Animal Science, 2008)
The effects of diets with different starch sources on the total tract apparent digestibility and glucose and insulin responses in cats were investigated. Six experimental diets consisting of 35% starch were extruded, each containing one of the following ingredients: cassava flour, brewers rice, corn, sorghum, peas, or lentils. The experiment was carried out on 36 cats with 6 replications per diet in a completely randomized block design. The brewers rice diet offered greater DM, OM, and GE digestibility than the sorghum, corn, lentil, and pea diets (P < 0.05). For starch digestibility, the brewers rice diet had greater values (98.6%) than the sorghum (93.9%), lentil (95.2%), and pea (96.3%) diets (P < 0.05); however, starch digestibility was > 93% for all the diets, proving that despite the low carbohydrate content of carnivorous diets, cats can efficiently digest this nutrient when it is properly processed into kibble. Mean and maximum glucose concentration and area under the glucose curve were greater for the corn-based diet than the cassava flour, sorghum, lentil, and pea diets (P < 0.05). The corn-based diets led to greater values for the mean glucose incremental concentration (10.2 mg/dL), maximum glucose incremental concentration (24.8 mg/dL), and area under the incremental glucose curve (185.5 mg.dL(-1).h(-1)) than the lentil diet (2.9 mg/dL, 3.1 mg/dL, and -40.4 mg.dL(-1).h(-1), respectively; P < 0.05). When compared with baseline values, only the corn diet stimulated an increase in the glucose response, occurring at 4 and 10 h postmeal (P < 0.05). The corn-based diet resulted in greater values for maximum incremental insulin concentration and area under the incremental insulin curve than the lentil-based diet (P < 0.05). However, plasma insulin concentrations rose in relation to the basal values for cats fed corn, sorghum, pea, and brewers rice diets (P < 0.05). Variations in diet digestibility and postprandial response can be explained by differences in the chemical composition of the starch source, including fiber content and granule structure, and also differences in the chemical compositions of the diets. The data suggest that starch has less of an effect on the cat postprandial glucose and insulin responses than on those of dogs and humans. This can be explained by the metabolic peculiarities of felines, which may slow and prolong starch digestion and absorption, leading to the delayed, less pronounced effects on their blood responses.
Keywords: digestion; feline; Ingredient; meal response test; Starch